Web-Based Employee Attendance System Development Using Waterfall Method (Journal of Advances in Information Systems and Technology, 2021)
Employees are one of the important elements in carrying out the duties and functions of the Pemalang Regency Communication and Information Department (Diskominfo). However, the management of employee data for recording the attendance of Non Pegawai Negeri Sipil (Non PNS) employees at Diskominfo Pemalang Regency is still done manually so it is not effective and efficient. Therefore, it is necessary to create an Employee Presence System that can manage employee attendance data. The goal is to facilitate the process of managing employee attendance data and make attendance data more accurate. The data collection method used in making the system is an interview. In the interview, consultations and direct questions and answers were conducted with the field supervisor regarding the system requirements to be made. Making this system using the waterfall method. The waterfall method is carried out sequentially from one phase to another. There are five phases in the waterfall method, namely requirements analysis, system design, implementation, system testing, and operation and maintenance. From making a system with this method, an employee attendance system is produced that can manage employee attendance data at the Communication and Information Department of Pemalang Regency.